A DISCOURSE ANALYSIS OF MEMES - Zubaidah, Neneng; Ardelia, Irena (Getsempena English Education Journal, 2018)
AbstractPeople nowadays use memes from internet to express their thought. Memes are pictures that consist of image/s and text that usually used in the internet whether it is just to entertain or have the specific purpose/s behind it. People can easily find and create memes in the internet using certain website. Memes have many deep meaning that people cannot understand without knowing the social content of it. In order to find out the deep meaning or the purpose of the memes, this study was conducted to analyse the relationship between picture and text in the memes with the meaning and the social function of it. The writer chose five famous and best memes randomly from the Google picture used keyword âbest memesâ as sample. The memes are taken randomly based on the needs of this research. Then the memes, as samples, were analysed using critical discourse analysis. Critical discourse analysis itself can be defined as âabove the sentenceâ or âbeyond the sentenceâ. It means itâs not only about the structure of the sentence but also about the meaning and the power behind the sentence. Finally after analyzing it, the writers found that memes are created with many purposes not only based on humour but also for express somebodyâs feeling or even to give sarcasm to others.Â Keywords: Critical Discourse Analysis, Memes